The Effectiveness of Get Skado App (Gadget Srabut Kelapo Dorong) to Increase Traffic Knowledge In Children - Nofrans Eka Saputra; Yun Nina Ekawati (Universitas Ahmad Dahlan, 2022)
Increasing knowledge about traffic is one solution to reduce the number of traffic accidents, especially for children. This research aimed to figure to examine the effectiveness of Get Skado App to increase traffic knowledge in children. The method used was a quasi-experiment with a pre-post control group design. The population of this research consists of 18 kindergarten students which were split into an experimental group and a controlled group. The experimental group was given Get Skado treatment. To measure the result, there was a traffic knowledge scale used in the pretest and posttest. The result was analyzed by using an independent t-test sample and paired t-test sample. The result of the research showed that there was significant traffic knowledge between pretest and post-test scores within the experimental group. Meanwhile, within the controlled group, no significant traffic knowledge was found. It can be concluded that Get Skado app can increase the traffic knowledge in children.Keywords:trafficÂ knowledge, Children, get skado